National security priorities: from jihad to the extreme-right? - Lopes, J. (EuroDefense Portugal, 2022)
Are Western governments changing their counter-terrorism focus: from jihad to the extreme-right? In this text, we briefly address this question focussing especially on the EU context and highlight how the activities of the extreme-right are becoming a very serious threat to member-states. The analysis follows three dimensions: (1) terrorist attacks; (2) Modus operandi and propaganda; (3) Radicalisation and recruitment.